Optimizing the Role of Bhabinkamtibmas to Prevent Radicalism in the Context of Maintaining Kamtibmas in the Legal Area of ​​the Bandung Police - Rio Aditya (Tanggon Kosala, 2021)
The understanding of radicalism has been a major problem threatening Indonesia, where every occurrence of terrorism happening in Indonesia is generally done by radical groups. The police are supposed to have proactive action related to the threat of radicalism that continues to emerge in Indonesia. The police are not only limited to capturing and cracking down against the perpetrators of terrorism, but rather to prevent the action of terrorism by conducting a deradicalisation of the Indonesian population who have been exposed to radical understanding. This research aims to describe and analyse the prevention of radicalism and the factors that influence it through the role of Bhabinkamtibmas and describe how to optimize the role of Bhabinkamtibmas in order to prevent radicalism in the jurisdiction of Polrestabes Bandung. This research uses qualitative approaches and descriptive methods. Location of research in the jurisdiction of Polrestabes Bandung. Data collection techniques consist of interviews, observations and study documents. The data validity techniques use source triangulation, methods, investigators and theories. Data analysis techniques using data reduction, data serving and withdrawal of conclusions and verifications. The results showed that in the territory of Polrestabes Bandung there are potential and thresholds related to radicalism, can be seen from the number of radical groups that exist and do activities in the city of Bandung. Polrestabes of Bandung Prevention with the actions of proactive policing (community development, early detection, and mediation). Factors influencing the role of Bhabinkamtibmas are internal factors (organization, HR management, material support and organizational policy) and external factors (culture of the community of Bandung, support of other police functions, cooperation of cross-agency, and attention and support of the community). The role of Bhabinkamtibmas is not optimal, but Satbinmas Polrestabes Bandung in an effort optimisation refers to the police Promoter Program by conducting reforms in two areas (field of coaching and operations).